Nomenclature in the online reptile trade - Vanessa J. Lynn; David L. Roberts (Oryx, 2023)
The internet has expanded opportunities for wildlife traders to conduct business globally, but monitoring this activity is often challenging. As monitoring techniques frequently employ language-based searches for particular words, it is important to understand the language traders use, particularly the nomenclature used to refer to traded species. We recorded advert data from four UK websites, focusing on reptiles, which constitute a large proportion of the international pet trade. We analysed whether the language types used by advertisers to refer to individual reptiles were associated with certain trader characteristics. We found English common names were the most frequent name type used to refer to species, regardless of the geographical location of the seller and the CITES Appendix listing of the species. However, scientific names were recorded in twice as many adverts for threatened and Near Threatened species as in adverts for non-threatened species, and only scientific names were used for three families: Anguidae, Pseudaspididae and Sphaerodactylidae. These findings could inform the creation of tailored keyword detection tools, which must account for the numerous language types in use within online wildlife trade communities. Future studies should examine the nuances of language used by other online wildlife trader communities in other contexts, such as different online platforms or different languages. The ultimate aim of these language detection tools will be to track in detail trends in the online reptile trade, offering a better understanding of potentially unsustainable trade patterns and helping authorities to enforce laws against illegal online reptile trade.